2012
DOI: 10.1063/1.3693591
|View full text |Cite
|
Sign up to set email alerts
|

CO2 dissolution in water using long serpentine microchannels

Abstract: The evolution of carbon dioxide bubbles dissolving in water is experimentally examined using long microchannels. We study the coupling between bubble hydrodynamics and dissolution in confined geometries. The gas impregnation process in liquid produces significant flow rearrangements. Depending on the initial volumetric liquid fraction, three operating regimes are identified, namely saturating, coalescing, and dissolving. The morphological and dynamical transition from segmented to dilute bubbly flows is invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 21 publications
5
40
1
Order By: Relevance
“…This phenomenon validates the using of the unit cell model (Vandu et al, 2005). Actually, when the segmented slug flow turns into bubbly flow (Cubaud et al, 2012;Yue et al, 2008) due to strong dissolution, the slug length or the spacing between adjacent bubbles only increases a little. In this paper, experimental data were carefully chosen to assure that all the bubble lengths were larger than channel width.…”
Section: Dissolution Ratementioning
confidence: 54%
“…This phenomenon validates the using of the unit cell model (Vandu et al, 2005). Actually, when the segmented slug flow turns into bubbly flow (Cubaud et al, 2012;Yue et al, 2008) due to strong dissolution, the slug length or the spacing between adjacent bubbles only increases a little. In this paper, experimental data were carefully chosen to assure that all the bubble lengths were larger than channel width.…”
Section: Dissolution Ratementioning
confidence: 54%
“…Generally, the gas hold‐up correlation for microchannels as a function of the gas volumetric quality can be classified into two types 24 ; linear relationship of the Armand‐type α = Cβ and nonlinear relationship of α = C 1 β 0.5 /( 1 −C 2 β ) . Which type describes well the gas hold‐up is mainly dependent on the channel size .…”
Section: Resultsmentioning
confidence: 99%
“…Gas‐liquid processes are widely involved in chemical industry. Many researches have shown that microreactors have unique advantages for various gas‐liquid system, such as absorption and reaction . For the design and operation of gas‐liquid microreactors, a great number of studies dedicated to two‐phase hydrodynamics and mass transfer in microchannels have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Current MF studies of CO 2 can be divided into two major categories: 1) experiments that utilize time‐dependent reduction in volume of gaseous CO 2 plugs, due the transfer of CO 2 molecules in adjacent liquid segments (Figure 2) and 2) experiments conducted with supercritical CO 2 (sc‐CO 2 ) without optically detectable shrinkage of sc‐CO 2 droplets (and sometimes, using sc‐CO 2 in a single‐phase configuration). Most MF studies within the first category have focused on the exploration of physical dissolution of CO 2 in aqueous56, 57, 75 or organic54, 55, 58 solvents. We note that although CO 2 reacts with water, because of the small value of the equilibrium constant (4.4×10 −7 at pH<1076), it can be assumed that the dominant species in the aqueous solution are the physically dissolved CO 2 molecules.…”
Section: Introduction To Droplet Microfluidicsmentioning
confidence: 99%